Anxiety and Sleep Quality Among Tuberculosis Patients: Evidence from Sitopeng Puskesmas, Cirebon City - Kasmad (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Tuberculosis (TB) is an infectious disease with high prevalence in Indonesia, often accompanied by psychological problems such as anxiety that may affect sleep quality. This study aimed to analyze the relationship between anxiety and sleep quality among TB patients in the working area of Sitopeng Puskesmas, Cirebon City. Method: This study used a descriptive correlational design with a cross-sectional approach. The total population of 40 TB patients was sampled using total sampling, resulting in 32 respondents. Anxiety was measured using the Hamilton Rating Scale for Anxiety (HRS-A), and sleep quality was assessed through a validated questionnaire. Data were analyzed using Chi-Square test with significance level of α=0.05. Results: Of the respondents, 75.0% experienced no anxiety, 6.3% had mild anxiety, 6.3% moderate anxiety, and 6.3% severe anxiety. Regarding sleep quality, 68.8% of patients had good sleep quality, while 31.2% had poor sleep quality. The analysis showed a significant relationship between anxiety and sleep quality (p = 0.009). Conclusion: There is a significant relationship between anxiety and sleep quality among tuberculosis patients. It is suggested that nurses provide psychological support and sleep hygiene education for TB patients to improve their well-being.